PEMANFAATAN IPTEK PADA USAHA MIKRO MINUMAN DAN INSTAN HERBAL DI KOTA SURAKARTA - Indrasari, Anita; Suparti, Erni; Wahyudi, Adhie Tri (LPPM UNS, 2017)
The purpose of this program is to solve the production and management problems experienced two micro entrepreneurs who produce instant herbs and herbal drinks in Solo, namely Jamu At Tiin and Yenny’s Natural Beverages Home Industry. The production problems are limited tool resource that causes length of processing time, labor fatigue and ineffectiveness of the production process. Management problem faced by both partners is a problem of marketing their products. First partner’s products marketed through direct deposited at pharmacies around, and the second partner’s products marketed limited by waiting for customers to come to the house to buy their products. Improvements that purposed to overcome the production problems are repairing production process through providing working tools such as instant mixer and herbal grinder. Improvements on management area are with the provision of an online store website along with operational training for first partners and the provision of mobile booth as an increase in marketing tools for second partners. After service activities is carried out, obtained improved performance in the form of reduced processing time, good mixing of raw materials and the instant herbal milling process, and reduced operator fatigue due to the mixing process is done the machine. In terms of marketing, the first partner’s market area become increased, second partner’s marketing also becomes easier and more flexible.Keywords: herbal, instant mixer, grinder, online